A CRITICAL ANALYSIS OF THE RELATIONSHIP BETWEEN ANTHROPOMETRIC INDICATORS OF OBESITY AMONG THE POST GRADUATE GIRLS (18-22 YEARS) - Mishra, Vandana (International Journal of Research -GRANTHAALAYAH, 2018)
Asians Indian are commonly dyslipidemia and predisposed to develop accelerated arthrosclerosis. The present study was done to critical analyze of the different anthropometric indicators of obesity such as body mass index, waist – hip ratio and waist circumference. The sample comprised of 150 females (mean age = 20.6 years) selected randomly from post graduate student of Banasthali University. A questionnaire was framed to collect the information from the respondent such regarding personal profile, physical activity and dietary pattern, different anthropometric measurements (height, weight, waist and hip circumference), BMI and WHR were calculated using standard techniques. The results of the study revealed that mean value of BMI and WHR of all respondents were 20.80 and 0.78 respectively. The result showed that according to BMI 49.3 per cent of respondents were normal while 1.3 per cent of respondents were in obese category. According to WHR prevalence of obesity was seen in 14.76 per cent of respondents. They all had risk of obesity associated diseases and other metabolic disorder while 83.39 per cent of the respondents had normal waist circumference they had no risk of metabolic complication. Thus, the study shows WHR is more useful and simple anthropometric indicator of obesity.